2021
DOI: 10.1007/s10508-021-01921-0
|View full text |Cite
|
Sign up to set email alerts
|

Geosocial Networking Apps Use Among Sexual Minority Men in Ecuador: An Exploratory Study

Abstract: Geosocial networking applications (GSN apps) have become important socialization contexts for sexual minority men (SMM). Despite their popularity, there is limited research carried out in Latin American countries and no single previous study done in Ecuador. To fill this gap, this exploratory study described and analyzed the relationships between the sociodemographic characteristics of SMM using GSN apps, their sought and fulfilled expectations, profile shared and sought characteristics, and the evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…However, in this article, we analyzed data from the 284 participants who reported having sexual encounters with other app users they met. Other results from this study are reported elsewhere (Hermosa-Bosano et al, 2021 ).…”
Section: Methodssupporting
confidence: 85%
“…However, in this article, we analyzed data from the 284 participants who reported having sexual encounters with other app users they met. Other results from this study are reported elsewhere (Hermosa-Bosano et al, 2021 ).…”
Section: Methodssupporting
confidence: 85%
“…Research on apps use by MSM is conducted worldwide. Examples of this include studies from Australia [37], Brazil [38,39]; Canada [40], China [41][42][43][44][45][46][47], Ecuador [48,49], England [50], Japan [51], the Netherlands [52], the Philippines [53] and Spain [54,55]. Most of these studies explored topics such as users' experiences connecting with others through apps, engaging in high-risk behaviors, and using apps for obtaining sexual health and HIV prevention information, as well as the opportunities provided for promoting HIV testing and linkage to HIV treatment via apps to users.…”
Section: Plos Onementioning
confidence: 99%